Family environment on emotional, social, and academic adaptation of adolescents: A study of middle school students - Vahid Motamedi (Intelektual Pustaka Media Utama, 2020)
Maintaining a positive relationship among family members creates a harmonious learning environment. When children are nurtured in such surroundings, they are likely to increase their emotional, social, and academic accomplishments and learn more effectively. The purpose of this paper was to analyze the familial role in emotional, social and academic adaptation of middle school students. The sample consisted of 9,728 middle school students from different parts of a Middle East country. The size of the sample was determined using multistage random sampling. Data were obtained using an emotional, social and academic survey and a family structure questionnaire. The study showed that most students have average or better behavior adaptation. Moreover, healthy family structures, favorable economic situation, and high-end paternal professions facilitate behavior adaptation. On the other hand, maternal employment has no effect upon behavior adaptation.